Estudo toxicológico comparativo da toxicidade do oxicloreto de cobre em tilápia vermelha (Oreochromis spp) e guaru (Poecilia reticulata) - Boock, Marcello Villar [UNESP] (2003)
The objectives of this work were to calculate of the fungicide copper oxychloride LC50 - 96 hours for the hybrid red tilapia (Oreochromis spp) and for the guaru (Poecilia reticulata), and to evaluate the intoxication risks due to environmental contamination and to copper bioconcentration. In the tests of acute toxicity, the red tilapia and the guaru were exposed to increasing concentrations of the fungicide in the water for 96 hours in static system. The LC50 were calculated based on mortality observed on tests. The intoxication risks due to the environmental contamination (EEC) were classified comparing the Estimated Environmental Contamination (EEC) with 100; 50; 25; 12,5; 6,25 and 3,125% of the lower and the highest doses of the fungicide recommend for agricultural cultures and comparing them to LC50 calculated. For copper bioconcentration determination on fishes the experiments lasting 15 days of duration were carried out and divided accordingly to accumulation and purification phases. The tilapias were exposed to 0,0769 and 69 0,0200 mg mg/L copper and guarus to 0,0200 and 0,0006 copper concentrations. The LC50 for red tilápia were of 129,21 mg/L of copper oxychloride and of 0,10 mg/L copper oxychloride, for guarus. The risks of intoxication of red tilapia due to the environmental contamination with copper oxychloride were low. The risk for guaru varied from high to moderate. Both species accumulated copper in the tested concentrations, whereas this was eliminated in the purification phase